581 Renal Arteriovenous Fistula Percutaneous Embolization Using the Amplatzer Vascular Plug II. (12th October 2021) - Soliman, H; Abdel-Aal, A; Elsabbagh, A; Hamed, M; Underwood, E; Saddekni, S
Abstract: Introduction: Renal arteriovenous fistula (AVF) is not considered a common condition; however, it can occasionally complicate with renal impairment and heart failure secondary to high cardiac output. Recently, percutaneous embolization has overcome traditional surgery as the first line of its management, because of better success rates as well as less morbidity and mortality. Case report: A 68-year-old male who presented with a renal AVF post left partial nephrectomy associated with a large pseudoaneurysm. This was found on a computed tomography angiography (CTA) scan, a routine follows up for his endovascular aortic aneurysm repair. Due to the patient's co-morbidities and to avoid the potentially fatal pseudoaneurysm rupture, a minimal invasive approach was agreed in the multidisciplinary meeting. He was treated by percutaneous transcatheter embolization using the Amplatzer Vascular Plug II (AVP-II) through a right femoral arterial access. The patient recovery was uneventful, following an overnight stay he was discharged home. CTA done four and ten months later showed the AVP-II device inside the left renal artery branch feeder with no artifacts seen. There was absence of recanalization of the AVF. In the literature, adopting the transarterial route for the renal AVF treatment with AVP-II device as a single embolotherapy device has not been reported before. Conclusions: Our report display the feasibleness of AVP-II in renal AVF treatment by arterial feeder embolization, specifically in fistulas with high flow and short communication as our case in which it showed offered multiple advantages over coils and is more cost effective.